2013
DOI: 10.4236/abb.2013.46a007
|View full text |Cite
|
Sign up to set email alerts
|

Increased myo-inositol in the posterior cingulate cortex in first-episode major depressive patients

Abstract: Major depressive disorder (MDD) is a severe, disabling pathology characterized, in addition to affective, cognitive and motor symptoms, by self-focused attention and rumination. During recursive self-focused processes and rumination, the posterior cingulate cortex (PCC) is activated. In vivo proton magnetic resonance spectroscopy (MRS) is a noninvasive imaging technique that can directly assess living biochemistry in localized brain regions. The aim of this study, therefore, was to use 1 H-MRS as a means of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Although differential MI content has been reported depending on the model species and brain regions [ 49 , 50 , 51 , 52 ] or age [ 53 , 54 , 55 ], MI has been suggested as a metabolic marker for depression [ 56 ]. In line with this, the classical ROC analysis in our study identified MI as the best candidate to discriminate CSIS from controls.…”
Section: Discussionmentioning
confidence: 99%
“…Although differential MI content has been reported depending on the model species and brain regions [ 49 , 50 , 51 , 52 ] or age [ 53 , 54 , 55 ], MI has been suggested as a metabolic marker for depression [ 56 ]. In line with this, the classical ROC analysis in our study identified MI as the best candidate to discriminate CSIS from controls.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence suggests that the processes of seeking and extracting information from autobiographical memory are linked to over-recruitment of the PCC regions (Leech & Sharp, 2014 ). Several studies have also shown that pathological rumination and attentional self-focusing in depression is governed by the activity pattern of PCC (Cheng et al ., 2018 ; Granados-Domínguez et al ., 2013 ). The abnormal activity in the sgPFC may reflect a maladaptive pattern of self-referential thought with rumination that is associated with a heightened risk of depression and other mental illnesses.…”
Section: Neural Correlations Between Emotion Dysregulation and Cognit...mentioning
confidence: 99%